Health-improving action effects of the system of P. K. Ivanov and Breathing Technique on the method of K. P. Buteyko for people of different age (from the long-term experience of the author) - Хорошуха, Михайло Федорович (Slobozhanskyi Herald of Science and Sport, 2016)
Khoroshukha M. Purpose: estimate efficiency of using of the system of Porfiry Ivanov and Breathing Technique on the method of K. P. Buteyko in health promotion for people of different age and physical condition. Material & Methods: there were 160 adult persons (113 women and 47 men) on the age of 36–54 years with different physical condition under our supervision. All the researches were provided on the ground of Brovarskyi city club of natural health improvement of people using the system of P. K. Ivanov «Vodoliy» (Water Bearer) (Kyiv region). There were applicable theoretical methods (includes analysis and synthesis of scientific and methodical literature), empirical method (includes functional and psychophysiological analyses) and statistics methods. Results: there were also indicated positive matters in the dynamics changes in indicators of the physical health. Conclusions: there were proved that, health-improving system of P. K. Ivanov and Breathing Technique on the method of K. P. Buteyko reasonable for practical use on filling of take on the purpose of health-improving action effects for people of different age.